Booktokers e transformação literária : como o TikTok formou comunidades literárias digitais e impactou o mercado editorial - Mattos, Gabriel Rangel de (2025)
This research project aims to analyze the impact of Booktokers, TikTok influencers focused on literary content, on the formation of digital communities and the Brazilian publishing market. The study focuses on understanding how the recommendations and interactions promoted by these influencers shape the reading habits of Generation Z, promoting literary works and strengthening the "Young Adult" genre. Additionally, it explores how these digital spaces revitalize literary criticism, traditionally dominated by professional critics, by offering a fresh, engaged perspective that directly resonates with young audiences. Using a qualitative approach, this research employs in-depth interviews with editors, influencers, and Generation Z readers, applying Content Analysis methodology to identify and categorize themes emerging from these interactions. The analysis seeks to highlight how Booktokers' discursive practices and digital communities foster a sense of belonging, influence consumption choices, and transform the reading experience into a social and cultural act. Drawing on theoretical contributions on cyberspace and the creative economy, the study aims to understand the BookTok phenomenon as a new form of creator economy that directly impacts the literary market, emphasizing the value of user-generated content in a media convergence scenario.